2018
DOI: 10.1017/s0714980818000260
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Attitudes and Knowledge of Social Work and Nursing Students on Later-Life Sexuality

Abstract: We examined ageist beliefs, attitudes, and knowledge towards sexuality in later life among 148 nursing students and 137 social work students in their first year of studies. The students completed the Fraboni Scale of Ageism, the Attitudes and Knowledge towards Older Adults' Sexuality Scale, and questionnaires regarding contact with older adults, prior sexual education, and socio-demographics. The results indicated that nursing students have more conservative attitudes towards older adults' sexuality. Ageist be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
3
0
6
Order By: Relevance
“…Studies suggest there is a gap between explicit and implicit attitudes towards sexual expression in later life. Studies that surveyed explicit attitudes towards sexuality in later life were conducted by close-ended question surveys such as the Aging Sexual Knowledge and Attitudes Scale (ASKAS) by White (1982) which directly addressed attitudes towards later-life sexuality (e.g., Di Napoli, Breland, & Allen, 2013;Ewen & Brown, 2012;Filiz Adana et al, 2015;Flaget-Greener, Gonzalez, Sprankle, Gonzalez, & Are, 2015;Gewirtz-Meydan, Even-Zohar, & Werner, 2018;Mahieu et al, 2016;Syme & Cohn, 2016). Each of these studies used self-report methodologies and required participants to state their explicit attitudes towards later-life sexuality on a ranking scale.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest there is a gap between explicit and implicit attitudes towards sexual expression in later life. Studies that surveyed explicit attitudes towards sexuality in later life were conducted by close-ended question surveys such as the Aging Sexual Knowledge and Attitudes Scale (ASKAS) by White (1982) which directly addressed attitudes towards later-life sexuality (e.g., Di Napoli, Breland, & Allen, 2013;Ewen & Brown, 2012;Filiz Adana et al, 2015;Flaget-Greener, Gonzalez, Sprankle, Gonzalez, & Are, 2015;Gewirtz-Meydan, Even-Zohar, & Werner, 2018;Mahieu et al, 2016;Syme & Cohn, 2016). Each of these studies used self-report methodologies and required participants to state their explicit attitudes towards later-life sexuality on a ranking scale.…”
Section: Introductionmentioning
confidence: 99%
“…Health professionals who were males and older with more years of working experiences, possessed permissive attitudes and better knowledge in some studies (Chen et al, 2017;Flaget-Greener et al, 2015;Helmes et al, 2012;Lee & Yoo, 2016;Mahieu et al, 2016). Unlike other studies where younger professionals were more likely to keep up with current knowledge on sexuality in older people (Evangelist et al, 2019), have fewer ageist beliefs, especially if they had contacts with older people e.g., grandparents (Gewirtz-Meydan et al, 2018), and be openminded and keen to pursue topics regarding the older LGBTI community (Hardacker et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…This highlights that ASKAS has its own limitations in assessing healthcare professionals' knowledge and attitudes towards sexuality in older people. In particular, the ASKAS lacks items about same-sex relationships with some of them phrased strictly for one gender and directly referring to heterosexuality (Gewirtz-Meydan et al, 2018;Helmes et al, 2012;Mahieu et al, 2016). Although ASKAS is a psychometrically sound measurement to assess knowledge of sexuality in ageing and is commonly used in many studies, Langer-Most and Langer ( 2010) indicated that the ASKAS may not effectively reflect current knowledge of sexuality in ageing, suggesting there may be construct validity issues.…”
Section: Discussionmentioning
confidence: 99%
“…Nos currículos, esse conteúdo é limitado (Cappiello et al, 2017) e não é considerado prioridade (Moreira et al, 2018). Pesquisas realizadas com acadêmicos da área da saúde são, em sua maioria, internacionais e têm demonstrado que eles possuem pouco conhecimento sobre comportamento sexual e IST em pessoas idosas e que suas atitudes são negativas (Chu et al, 2020;Gewirtz-Meydan et al, 2018;Wilschut et al, 2021).…”
Section: Introductionunclassified
“…Nesse sentido, na literatura não há consenso em relação aos fatores associados ao conhecimento e às atitudes de acadêmicos de enfermagem em relação à sexualidade na velhice. Do que se sabe, a idade de acadêmicos, o contato prévio com pessoas idosas (Chu et al, 2020;Gewirtz-Meydan et al, 2018) e o período do curso Wilschut et al, 2021) estão associados ao conhecimento dos acadêmicos. Em relação às atitudes, idade, contato prévio com pessoas idosas21 e período do curso (Chu et al, 2020) também foram associados.…”
Section: Introductionunclassified